Soil N2O fluxes along an elevation gradient of tropical montane forests under experimental nitrogen and phosphorus addition - Müller, Anke K.; Matson, Amanda L.; Corre, Marife D.; Veldkamp, Edzo (Frontiers in Earth Science, 2015)
Nutrient deposition to tropical forests is increasing, which could affect soil fluxes of nitrous oxide (N2O), a powerful greenhouse gas. We assessed the effects of 35-56 months of moderate nitrogen (N) and phosphorus (P) additions on soil N2O fluxes and net soil N-cycling rates, and quantified the relative contributions of nitrification and denitrification to N2O fluxes. In 2008, a nutrient manipulation experiment was established along an elevation gradient (1000, 2000 and 3000 m) of montane forests in southern Ecuador. Treatments included control, N, P and N+P addition (with additions of 50 kg N ha−1 yr-1 and 10 kg P ha−1 yr-1). Nitrous oxide fluxes were measured using static, vented chambers and N cycling was determined using the buried bag method. Measurements showed that denitrification was the main N2O source at all elevations, but that annual N2O emissions from control plots were low, and decreased along the elevation gradient (0.57 ± 0.26 to 0.05 ± 0.04 kg N2O-N ha-1 yr-1). We attributed the low fluxes to our sites’ conservative soil N cycling as well as gaseous N losses possibly being dominated by N2. Contrary to the first 21 months of the experiment, N addition did not affect N2O fluxes during the 35-56 month period, possibly due to low soil moisture contents during this time. With P addition, N2O fluxes and mineral N concentrations decreased during Months 35-56, presumably because plant P limitations were alleviated, increasing plant N uptake. Nitrogen plus phosphorus addition showed similar trends to N addition, but less pronounced given the counteracting effects of P addition. The combined results from this study (Months 1-21 and 35-56) showed that effects of N and P addition on soil N2O fluxes were not linear with time of exposure, highlighting the importance of long-term studies.